TINGKAT KESIAPAN IMPLEMENTASI KNOWLEDGE MANAGEMENT PADA POLITEKNIK NEGERI SRIWIJAYA - Oktavianti, Euis (Masyarakat Telematika Dan Informasi : Jurnal Penelitian Teknologi Informasi dan Komunikasi, 2015)
Knowledge management works to increase the organizationâs ability to learn from their environment and combines the knowledge to business processes. However, to implement KM in an organization is not always easy and successful. Some literatures mention the aplication of KM was failed because of low KM. Some well preparation and readiness is required to make KM successful implemented. The measurement of readiness level is the first step to do. The research is aimed to find of the readiness by implementing Knowledge Management. The measurement is conducted by grouping the KMCSF into some Knowledge Management aspect. The method used to measure the level of KM is by mapping the KMCSF with KM infrastructure. The result shows that KM readiness at Politeknik Negeri Sriwijaya reaches 62,63% . It means that POLSRI is on the third level of KM, which means that POLSRI gets the predicate âreadyâ (accepted). To be concluded, POLSRI is ready to implement KM.